Carmello E. Palumbo, El Divorcio y la Familia, Congreso Nacional de Defensa de la Familia, Buenos Aires, 1984, 38 pp - Derisi, Octavio Nicolás (1984)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina